2017
DOI: 10.1515/rjr-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Nasolacrimal duct obstruction: the relationship with nasal allergy

Abstract: Nasolacrimal duct obstruction (NLDO) is a common event in clinical practice. The authors, all members of the Italian Society of Rhinology, analysed 100 cases from different ENT Departments. The causes of NLDO, according to the etiology, can be divided into two classes: idiopathic primary acquired nasolacrimal duct obstruction and secondary. The aim of the study was to describe an association between the sign and symptoms of chronic rhinosinusitis and a complaint of epiphora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…23 Passali et al stated that the chronic rhinosinusitis, in particular allergic rhinosinusitis, are one of specific predisposing factors to the development of NLDO. 24 Cervelli et al found a reduced flow of the medium contrast in nasolacrimal duct due to a partial obstruction at the level of the internal ostium in patients with septal deviations and turbinate hypertrophy. 10 Paulsen et al described the pathological changes leading to occlusion and fibrosis of lacrimal passage due to infectious process of nasal cavity.…”
Section: Discussionmentioning
confidence: 97%
“…23 Passali et al stated that the chronic rhinosinusitis, in particular allergic rhinosinusitis, are one of specific predisposing factors to the development of NLDO. 24 Cervelli et al found a reduced flow of the medium contrast in nasolacrimal duct due to a partial obstruction at the level of the internal ostium in patients with septal deviations and turbinate hypertrophy. 10 Paulsen et al described the pathological changes leading to occlusion and fibrosis of lacrimal passage due to infectious process of nasal cavity.…”
Section: Discussionmentioning
confidence: 97%